Hubungan Pengetahuan Tentang Antidiabetika Oral (ADO) dengan Karakteristik Demografi, Kepatuhan, dan Kontrol Gula pada Pasien Diabetes Mellitus Tipe 2 - Nanda Puspita; Muliyandhayanti Muliyandhayanti; Endah Cahyani (Jurnal Sehat Mandiri, 2020)
The rise of diabetes mellitus (DM) prevalence requires intensive care and self-care as a key to achieve targeted glycemic control. Patients' knowledge about DM treatment is a supportive factor of achieving the target. This study was conducted to determine the relationship between patient’ knowledge of oral antidiabetics (ADO) and demographic characteristics, adherence as well as clinical conditions of diabetes mellitus patients. A cross-sectional design was applied by interviewing 100 outpatients in an Integrated Diabetes Service Unit (UPDT) in Hospital X. The sampling technique used was consecutive sampling. Knowledge is measured by a structured questionnaire guided by the education 'Ask 5 O' about drugs. The results showed that the majority of diabetic patients knew the name (74%) and efficacy (100%) of the antidiabetic drugs being used, but they poorly understood how to use the drug (58%) and barely knew the side effect (11%). Bivariate analysis showed a significant relationship between demographic factors, namely age (p = 0.005) and education level (p = 0.025) and patient’s medication knowledge. However, there was no significant relationship between patient’s medication knowledge and medication adherence (p = 0.592) and HbA1c as glycemic control (p = 0.101). It can be concluded that drug knowledge in patients does not determine medication adherence and glycemic control. analysis of other factors such as patient perceptions of medication and complication conditions that may be closely related to medication adherence and sugar control is suggested.